2015
DOI: 10.1016/j.clinbiomech.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underpinning the peak knee flexion moment increase over 2-years following arthroscopic partial meniscectomy

Abstract: L., Mechanisms underpinning the peak knee flexion moment increase over 2-years following arthroscopic partial meniscectomy, Clinical Biomechanics (2015Biomechanics ( ), doi: 10.1016Biomechanics ( /j.clinbiomech.2015 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…The vKRF represents an equal and opposite vertical force acting between the tibia and femur, without accounting for muscle forces (12). Finally, although gait speed and measures of body size do not directly reflect joint loading, these are main effectors of the vertical ground reaction force (13), a primary determinant of the KAM, KFM, and vKRF (12,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The vKRF represents an equal and opposite vertical force acting between the tibia and femur, without accounting for muscle forces (12). Finally, although gait speed and measures of body size do not directly reflect joint loading, these are main effectors of the vertical ground reaction force (13), a primary determinant of the KAM, KFM, and vKRF (12,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, extent of meniscal resection is known to be proportionally correlated with increased tibiofemoral contact pressures of up to 80% to 90%, and directly affects knee biomechanics and kinematics. [19][20][21][22][23] Extent of meniscal resection may also modulate functional outcomes by altering knee kinematics, including increased knee adduction, flexion, and extension moments, [24][25][26] as well as knee extensor strength. [27][28][29] Conclusions Roughly 1 in 2 runners return to their preoperative running frequency after undergoing APM.…”
Section: Limitationsmentioning
confidence: 99%
“…In 1948, Fairbank[ 8 ] reported the clinical outcomes of 107 patients after total meniscectomies and found degenerative knee changes in most of them. From then, several other studies demonstrated the detrimental effects of total meniscectomies on knee joint[ 9 - 13 ]. These studies significantly changed the treatment approach of meniscus tears.…”
Section: Introductionmentioning
confidence: 99%